Illness caused by tuberculosis among health professionals in a municipality in the North Region of Brazil (Research, Society and Development, 2021)
Objective: To analyze the illness caused by tuberculosis among health professionals in a municipality in the Northern Region of Brazil. Methodology: This is a cross-sectional descriptive study, using a quantitative approach, carried out based on the survey of sociodemographic, clinical and treatment variables, in the Information System for Notifiable Diseases, in the period from 2015 to 2018, and analyzed through the distribution of frequency, after complying with ethical precepts. Results: Of the 40 cases of TB among health professionals during the analyzed period, the majority belonged to the female sex, between the age group of 31 to 40 years old, self-declared brown, with complete high school, did not present associated diseases and conditions, were reported in 2016, new cases, with clinical pulmonary form, suspected chest X-ray, negative sputum smear microscopy, sputum culture and rapid molecular test for TB not performed, blank/ignored sensitivity test, HIV negative, notification in tertiary referral or in Primary Health Care, with two contacts identified and none examined, failure to perform Directly Observed Treatment for TB, sputum smear microscopy for monthly control until the third month, mean treatment time of 177 days, low percentage of cure and high for abandonment. Conclusion: Such findings allow a reflection on the effectiveness of the strategies implemented for worker health surveillance and the challenges that permeate the structure of health services for the control of the disease.